Wartość jako istota kapitału - Iwin-Garzyńska, Jolanta (Value as an Essence of Capital, 2007)
The aim of the article is to indicate in definitions of capital its financial essence and to explain what capital really is. Therefore it is important to show value as an essence of capital and to emphasize its financial aspect. Capital in financial meaning is a result of cash flows from owners and debtors to the firm. Capital is materialized and achieve the value in the assets, works in them and as a consequence rises its value in the form of financial surplus (the net profit an amortization capital).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 231-236